The past, present and future of technology in PSP: Preliminary results - Morgado, Sónia M. A.; Felgueiras, Sérgio Ricardo Costa Chagas; Moura, Rui Coelho de (ISCPSI/ICPOL, 2024)
Technology is one of the critical resources for policing. The technology involves innovation to enable security in a new and effective way. Technology in Police Institutions – TechPol – is linked to mission-oriented security objectives. In this context, the primary inquiries of this study revolve around questions. What are the technologies in place in Public Security Police (PSP)? How many projects are under implementation or have been implemented? What is the level of knowledge about TechPol in PSP?
Keywords: Polícia; Ciências Policiais; ISCPSI; Ensino Superior Policial